2010
DOI: 10.1126/science.1189095
|View full text |Cite
|
Sign up to set email alerts
|

The Fusogen EFF-1 Controls Sculpting of Mechanosensory Dendrites

Abstract: The mechanisms controlling the formation and maintenance of neuronal trees are poorly understood. We examined the dynamic development of two arborized mechanoreceptor neurons (PVDs) required for reception of strong mechanical stimuli in Caenorhabditis elegans. The PVDs elaborated dendritic trees comprising structural units we call "menorahs." We studied how the number, structure, and function of menorahs were maintained. EFF-1, an essential protein mediating cell fusion, acted autonomously in the PVDs to trim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
267
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 169 publications
(280 citation statements)
references
References 18 publications
12
267
1
Order By: Relevance
“…The fusion protein EFF-1 mediates dendrite retraction and auto-fusion of excess branches by a novel cell-autonomous pruning mechanism (Oren-Suissa et al, 2010). Thus, this fusogen maintains the structural units by trimming excess branching during normal developmental arborization (Oren-Suissa et al, 2010). AFF-1, a paralog of EFF-1, is a second C. elegans fusogen displaying a more restricted tissue distribution pattern (Avinoam and Podbilewicz, 2011;Sapir et al, 2007); AFF-1 was not found to be involved in PVD remodeling during development (Oren-Suissa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The fusion protein EFF-1 mediates dendrite retraction and auto-fusion of excess branches by a novel cell-autonomous pruning mechanism (Oren-Suissa et al, 2010). Thus, this fusogen maintains the structural units by trimming excess branching during normal developmental arborization (Oren-Suissa et al, 2010). AFF-1, a paralog of EFF-1, is a second C. elegans fusogen displaying a more restricted tissue distribution pattern (Avinoam and Podbilewicz, 2011;Sapir et al, 2007); AFF-1 was not found to be involved in PVD remodeling during development (Oren-Suissa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The fusion protein EFF-1 mediates dendrite retraction and auto-fusion of excess branches by a novel cell-autonomous pruning mechanism (Oren-Suissa et al, 2010). Thus, this fusogen maintains the structural units by trimming excess branching during normal developmental arborization (Oren-Suissa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, mec-3, which encodes a LIM homeodomain transcription factor expressed in PVD neurons (Way and Chalfie, 1988;Way and Chalfie, 1989), as well as eff-1, which encodes a protein essential for cell fusion, are the only genes known to be required for the elaboration of PVD dendritic arbors (Oren-Suissa et al, 2010;Tsalik et al, 2003). By carrying out two RNAi screens, a small-scale candidate-based screen and a large-scale screen of chromosome IV, we identified 11 genes that either promote or suppress PVD dendrite branching.…”
Section: Introductionmentioning
confidence: 99%